The Influence of PK/PD on the Structure of Optimal Controls in Cancer Chemotherapy Models - Urszula Ledzewicz; Heinz Schättler (Mathematical Biosciences and Engineering)
Mathematical models for cancer chemotherapy as optimal control problems are considered. Results on scheduling optimal therapies when the controls represent the effectiveness of chemotherapeutic agents, or, equivalently, when the simplifying assumption is made that drugs act instantaneously, are compared with more realistic models that include pharmacokinetic (PK) equations modelling the drug's plasma concentration and various pharmacodynamic (PD) models for the effect the concentrations have on cells.